2019
DOI: 10.1002/ppul.24276
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia in preterm infants: Measurement using the desaturation index

Abstract: Objective The aims of this study were to: (i) Determine in preterm infants at neonatal discharge the prevalence of intermittent hypoxia (IH), as measured by the oxygen desaturation index (DSI) recorded by pulse oximetry and (ii) Determine the change in values for very preterm infants at 1‐month post discharge. Methods Preterm infants were recruited from the Wellington regional neonatal intensive care unit (NICU) and 24‐h pulse oximetry recordings performed immediately before discharge. Infants born <32 weeks g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…The prevalence and significance of intermittent hypoxemia on outcomes in preterm infants remains unclear but has been shown to be associated with poorer neurocognitive outcomes in older children with sleep disordered breathing . Previous studies have shown that the desaturation severity, or SpO 2 nadir, is likely to be significant but there is no consensus on what defines a severe desaturation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence and significance of intermittent hypoxemia on outcomes in preterm infants remains unclear but has been shown to be associated with poorer neurocognitive outcomes in older children with sleep disordered breathing . Previous studies have shown that the desaturation severity, or SpO 2 nadir, is likely to be significant but there is no consensus on what defines a severe desaturation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Care should be taken when interpreting any study with excessive signal artefact and these studies should be repeated rather than making a management decision based on a suboptimal recording. A significant limitation is the inability to identify if clusters of desaturations are secondary to periodic breathing, central apnoeas or obstructive apnoeas . Paediatric respiratory specialists can apply their PSG experience through the visual analysis and pattern recognition of abnormal SpO 2 and heart rate waveforms to determine who may require more formal assessment by PSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since publication of the ATS guidance [37] in 2018 the evidence base has expanded in relation to reference ranges for oxygen saturation parameters in healthy preterm and term infants [13,28,29,[46][47][48]. Using this data, we propose a structured weaning programme for infants with BPD at term equivalent age (TEA), receiving supplemental oxygen post-discharge from NICU.…”
Section: Setting Criteria For Oxygen Requirment At Dischargementioning
confidence: 99%